THE JAVANESE IN LAMPUNG, STRANGER OR LOCALS? WITH THE REFERENCE OF CHINESE EXPERIENCE - Riwanto Tirtosudarmo (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2015)
Javanese is the majority of the Indonesian population. Geographically they are resided in the provinces of Central Java, DIY and East Java. However, since the beginning of the 20th century the Dutch colonial government began to relocate them to Lampung in the sothern part of Sumatra and then to other places. Within a century Lampung become the main destination of Javanese migration, making Lampung the Javanese province after Central Java, DIY and East Java. Unlike the Chinese that is able to construct Chinese nation and state, the Javanese failed in constructing the Javanese nation, instead supporting the construction of Indonesian nation and state. In this article the Javanese in Lampung is exposed as the showcase of how Javaneseness as an identity is located within the post-Suhartos political development contexts, when decentralization and regional autonomy began to be implemented. Based on a fieldwork in Lampung, it shows that the Javanese while continue preserving the cultural identities yet reluctantly using their identities for political mobilization, for instance during the election of head of local government. The Javanese seems secure to be the majority, and not perceived themselves as strangers, although the resided in the land of the Lampuners.Keyword: Migration, Ethnic Identity, Local People, Political Mobility